Analisis Psikologi Sastra pada Novel Areksa Kajian Psikologi Sigmund Freud - Valentina Eka Amelia; Ahmad Ilzamul Hikam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to examine the personality structure of the characters in the novel Areksa written by ItaKrn by utilizing a literary psychology approach based on Sigmund Freud's psychoanalytic theory. This study focuses more on the characters of Areksa Dirgantara and Ilona Ladeika, who experience emotional dynamics through the interaction of the three components of personality: id, ego, and superego. The method applied in this study is descriptive qualitative, with data collection techniques that include in-depth reading and recording. The findings of this study indicate that the characters in the novel face significant internal conflicts, where emotional drives (id), rational considerations (ego), and moral values ​​(superego) influence each other in the decision-making process and attitude formation. Areksa is shown as a character trapped in a dilemma between love and faith, while Ilona depicts a struggle between personal desires and existing social norms. These results emphasize how relevant Freud's theory is in understanding psychological conflicts in literary characters. Thus, a literary psychology approach can explore the inner depths of characters and enrich understanding of literary works as a reflection of the complexity of human psychology.